Chosen Prey - Sandford, John (New York Berkley Books, 2002)
Hoping to use a supposedly straightforward case of murder to clear his mind, Deputy Chief Lucas Davenport finds himself matching wits with an ever-escalating serial killer, art history professor, congenial pervert, and sexual predator James Qatar.
Keywords: Serial murderers -- Police -- Serial murders